Estudio descriptivo sobre salud sexual y reproductiva en estudiantes de la UDLA durante el año 2018 - García Ramírez, José David (2020)
Background: In Latin America, the lack of access to knowledge about sexual and reproductive health has increased the rate of adolescent pregnancy, abortions, venereal disease transmission, increasing morbidity and mortality in adolescents and young adults. Currently, verbal communication, formal education together with digital media provide sexual and reproductive knowledge, reducing risky sexual behavior in adolescents and young adults as a tool of support networks. Objective: To describe the frequency of communication about sexual health and reproduction in students of the University of the Americas (UDLA). Methodology: Through a descriptive cross-sectional study of a universe of 14 341 people, enrolled in 2018. A sample of 125 UDLA students was obtained made up of 58% women and 42% men belonging to the various careers of this educational unit. Results: 69% of participants affirm having talked about sexuality with their parents, of which only 1% refer have had this dialogue for more than 5 occasions. 54% of participants did not She has had talks about sexuality for lack of trust with her parents. The 40% of participants who had talks about sexuality with their parents, they perceived that these presented a scientific support. Knowledge concerning sexual and reproductive health issues they are losing their condition taboo, therefore, students come more frequently with various professionals to satisfy your concerns. This is how 88% surveyed go to these professionals to avoid risky sex. Conclusion: UDLA students prefer to dialogue about sexual health and reproductive with their support networks, being their parents the main protagonists of these dialogues.